Biomarker-based approach to determine etiology and severity of pulmonary hypertension: Focus on microRNA - Rogula, Sylwester; Pomirski, Bartosz; Czyżak, Norbert; Eyileten, Ceren; Postuła, Marek; Szarpak, Łukasz; Filipiak, Krzysztof J.; Kurzyna, Marcin; Jaguszewski, Miłosz; Mazurek, Tomasz; Grabowski, Marcin; Gąsecka, Aleksandra (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary arterial hypertension (PAH) is characterized by remodeling of the pulmonary arteries, and defined by elevated pulmonary arterial pressure, measured during right heart catheterization. There are three main challenges to the diagnostic and therapeutic process of patients with PAH. First, it is difficult to differentiate particular PAH etiology. Second, invasive diagnostic is required to precisely determine the severity of PAH, and thus to qualify patients for an appropriate treatment. Third, the results of treatment of PAH are unpredictable and remain unsatisfactory. MicroRNAs (miRNAs) are small non-coding RNAs that regulate post transcriptional gene-expression. Their role as a prognostic, and diagnostic biomarkers in many different diseases have been studied in recent years. MiRNAs are promising novel biomarkers in PAH due to their activity in various molecular pathways and processes underlying PAH. Lack of biomarkers to differentiate between particular PAH etiology and evaluate the severity of PAH, as well as paucity of therapeutic targets in PAH open a new field for the possibility to use miRNAs in these applications. In our article, we discuss the potential of miRNAs use as diagnostic tools, prognostic biomarkers and therapeutic targets in PAH.